Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1002/(sici)1520-636x(1998)10:7<693::aid-chir15>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Lipase catalyzed transesterification of 2-substituted 3-hydroxy esters

Abstract: Kinetic resolution of 2‐substituted 3‐hydroxy esters was examined by lipase PS catalyzed transesterification using vinyl acetate as an acyl donor. Resolution of (±)‐syn‐ and ‐anti‐1a, ‐1e possessing a small methyl group at the C‐3 position was accomplished enantioselectively. The outcome of the resolution seems to be related to the differences in size of the substituents at the stereocenter bearing a secondary hydroxy group. Chirality 10:693–698, 1998. © 1998 Wiley‐Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…They have been prepared via lipase-catalyzed transesterification resolution of (R,S)-3-hydroxy carboxylic esters in organic solvents or hydrolysis at the 3-O-acyl group in the aqueous solution (Bornscheuer et al, 1993;Hoff and Anthonsen, 1999;Huerta and Backvall, 2001;Kaga et al, 1998;Nascimento et al, 2003;Xu and Yuan, 2005). However for the former, the separation of resultant products of 3-O-acyl ester from remaining substrates is tedious and difficult.…”
Section: Introductionmentioning
confidence: 99%
“…They have been prepared via lipase-catalyzed transesterification resolution of (R,S)-3-hydroxy carboxylic esters in organic solvents or hydrolysis at the 3-O-acyl group in the aqueous solution (Bornscheuer et al, 1993;Hoff and Anthonsen, 1999;Huerta and Backvall, 2001;Kaga et al, 1998;Nascimento et al, 2003;Xu and Yuan, 2005). However for the former, the separation of resultant products of 3-O-acyl ester from remaining substrates is tedious and difficult.…”
Section: Introductionmentioning
confidence: 99%
“…6 To this end, we envisioned to utilize lipase-catalyzed transesterification 7 of 2-substituted 3-hydroxy esters. A very few related studies were reported so far on lipase-catalyzed transesterifications of 3-hydroxy esters such as cis-1-ethoxycarbonyl-2-hydroxycyclohexane, 8 tert-butyl 3hydroxy-4-pentenoate, 9 4-aryloxy-3-hydroxy esters, 10 and syn-and anti-2-substituted 3-hydroxy esters 11 whose substituents at the C-2 position were severely limited to Ph-, MeS-, and PhS-groups. To the best of our knowledge, there has not been reported to date a general and efficient lipase-catalyzed transesterification for acyclic 2substituted 3-hydroxy esters.…”
mentioning
confidence: 99%
“…To our knowledge, DKR of β-hydroxy esters has not been reported but their kinetic resolution (KR) is known. , This is mainly due to the problems of isomerizing chiral β-hydroxy esters. An obvious limitation with KR is that the maximum theoretical yield of one enantiomer is 50% vs 100% with DKR .…”
mentioning
confidence: 99%
“…Although the presence of electron-donating groups in the aromatic ring has been observed previously to have a negative effect on the racemization process,6c the enantioselection in this particular case was excellent, >99% ee (entry 2), and compound 2b was isolated in 69% yield (based on aldehyde 5b ). Attempts to obtain enantio- and diastereoselection in compounds 2 with a methyl group in the α-position have so far been fruitless, due to the increased bulkiness next to the stereocenter (vide supra). 7c, Substitution of the phenyl group in benzaldehyde ( 5a ) with a benzyl group also resulted in an efficient DKR (entry 3). Cyclohexyl derivative 2d (entry 4) gave a low ee compared to that of aryl compounds 2a − c .…”
mentioning
confidence: 99%